Pengaruh Kualitas Barang dan Kepercayaan Terhadap Keputusan Pembelian Preloved Dalam Media Sosial Facebook Di Batam - Imelda Oey Banamtuan; Suhardi Suhardi (eCo-Buss, 2023)
In the current era of globalization, the development of technology and communication is growing rapidly and has become a very important issue for everyone. Technological advances in today's Indonesia make everything easier with the internet, by having a huge opportunity for business people to market their products online not only making it easier and saving time but also can be a loss for buyers if they are not careful when buying goods. This study aims to determine the effect of product quality and trust on preloved purchasing decisions on Facebook social media in Batam. The techniques used in this research are descriptive analysis and quantitative data analysis. The results of the study show that it has been concluded that it has a significant and simultaneous effect on the quality of goods and trust in preloved purchasing decisions on social media Facebook in Batam.